1996
DOI: 10.1152/jn.1996.76.4.2353
|View full text |Cite
|
Sign up to set email alerts
|

Decreased duration of Ca(2+)-mediated plateau potentials in striatal neurons from aged rats

Abstract: 1. The influence of age on striatal neuron Ca2+ physiology was studied through an analysis of intracellularly recorded Ca(2+)-mediated plateau potentials. In vitro brain slices from young and aged rats were treated with the K+ channel blocker tetraethylammonium (30 mM) to facilitate the expression of plateau potentials. A sample of neurons was also filled with biocytin and post hoc correlations were performed between morphology and physiology. 2. Testing of sampling parameters in neurons from young rats reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…Nonetheless, we found, as have others, that aged brain slices tended to show less activity and the neurons were more fragile during recording (Cepeda et al, 1992;Dunia et al, 1996). In a previous study from our laboratory, we examined the impact of in vitro processing on cell viability, using the trypan blue exclusion method for staining dead cells, and found no age difference in the number of dead striatal cells in brain slices (Dunia et al, 1996). Some of the brain slices from this study were included in the trypan blue analysis.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, we found, as have others, that aged brain slices tended to show less activity and the neurons were more fragile during recording (Cepeda et al, 1992;Dunia et al, 1996). In a previous study from our laboratory, we examined the impact of in vitro processing on cell viability, using the trypan blue exclusion method for staining dead cells, and found no age difference in the number of dead striatal cells in brain slices (Dunia et al, 1996). Some of the brain slices from this study were included in the trypan blue analysis.…”
Section: Resultssupporting
confidence: 82%
“…Biocytin-filled neurons were reacted for horseradish peroxidase (HRP) histochemistry according to previously published procedures (Dunia et al, 1996;Horikawa and Armstrong, 1988). Cell body dimensions and total dendritic length measurements were made using the Eutectic Neuronal Tracing System attached directly to a Nikon Microscope (EUTECTIC, Tujunga, CA).…”
Section: Intracellular Recording Staining and Morphological Measuremmentioning
confidence: 99%
“…Activated microglia also increase during normal aging in humans, in the absence of Alzheimer's disease or other specific neurodegenerative conditions (e.g., DiPatre and Gelman, 1997;Tompkins et al, 1997). In view of evidence for apoE and apoJ in the recycling of cholesterol and other membrane components after neural injury (Boyle et al, 1989;Poirier, 1994;Reeder et al, 1995), we suggest that the age-related increase of apoE, and possibly of apoJ, could reflect age-related increases in membrane remodeling, as implied by the 50% age-related loss of dendritic spine density in striatal interneurons (Dunia et al, 1996). For example, the decline of dopamine (D 2 ) receptors is detected by midlife (Morgan and May, 1990), concurrent with increased GFAP.…”
Section: Discussionmentioning
confidence: 83%
“…Because the two genotypes share a set of alleles from the F344 strain, the similar rate of GFAP increase with age could result from the dominance of one or more alleles from the shorter-lived F344 strain. Astrocyte age changes indicative of increased cell activities and gene activity are important because of opposite trends in many neuronal activities, e.g., agerelated decreases in dopamine receptor subtypes (Morgan and May, 1990;Zhang et al, 1995), in calciummediated plateau potentials, and in dendritic spine densities (Dunia et al, 1996). Conclusions about effects of aging on cell functions must be carefully developed for each cell type, e.g., in the liver, and other non-neural tissues many genes show marked decreases in transcription Van Remmen et al, 1994), which are opposite of the increases observed for three genes active in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation